Special Focus Introduction: Bodies, Transnationalism and Affect in Recent Hispanic Poetry - Enrique Álvarez (Studies in 20th & 21st Century Literature, 2020)
Introduction to special focus section: Bodies, Transnationalism and Affect in Recent Hispanic Poetry.
Keywords: Spanish poetry; affect theory; bodies; transnationalism